Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.138
|View full text |Cite
|
Sign up to set email alerts
|

Will it Unblend?

Abstract: Natural language processing systems often struggle with out-of-vocabulary (OOV) terms, which do not appear in training data. Blends, such as innoventor, are one particularly challenging class of OOV, as they are formed by fusing together two or more bases that relate to the intended meaning in unpredictable manners and degrees. In this work, we run experiments on a novel dataset of English OOV blends to quantify the difficulty of interpreting the meanings of blends by large-scale contextual language models suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The topic of this paper is related to the more fundamental question of how PLMs represent the meaning of complex words in the first place. So far, most studies have focused on methods of representation extraction, using ad-hoc heuristics such as averaging the subword embeddings (Pinter et al, 2020;Sia et al, 2020; or taking the first subword embedding (Devlin et al, 2019;Heinzerling and Strube, 2019;Martin et al, 2020). While not resolving the issue, we lay the theoretical groundwork for more systematic analyses by showing that PLMs can be regarded as serial dual-route models (Caramazza et al, 1988), i.e., the meanings of complex words are either stored or else need to be computed from the subwords.…”
Section: Introductionmentioning
confidence: 99%
“…The topic of this paper is related to the more fundamental question of how PLMs represent the meaning of complex words in the first place. So far, most studies have focused on methods of representation extraction, using ad-hoc heuristics such as averaging the subword embeddings (Pinter et al, 2020;Sia et al, 2020; or taking the first subword embedding (Devlin et al, 2019;Heinzerling and Strube, 2019;Martin et al, 2020). While not resolving the issue, we lay the theoretical groundwork for more systematic analyses by showing that PLMs can be regarded as serial dual-route models (Caramazza et al, 1988), i.e., the meanings of complex words are either stored or else need to be computed from the subwords.…”
Section: Introductionmentioning
confidence: 99%
“…Our experiment shows that popular word form encoders, such as ELMo or BERT's WordPiece, still have a long way to go in terms of recognizing the origins of a novel form. Errors at this stage might lead to inability to handle morphologically complex OOVs in downstream semantic applications (Pinter et al, 2020), although further study of such effects and of the utility of OOV classification in alleviating them is still necessary. Properly leveraging context for morphological decomposition of complex forms also remains an open problem.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, no work to date has explored how Transformer-based encoders represent compounds. The most relevant study in this direction is the one by Pinter et al (2020) reported an overall high similarity between the compound and the constituents, slightly increasing through the layers.…”
Section: Word Representation In Transformersmentioning
confidence: 96%